Geomagnetic Variables and US Market Descriptors as Predictors of the Frequency of Use of the Google Search Terms Anxiety, Depression, Peace and Dow Jones - Di Feo, Marco G.; Juden-Kelly, Lyndon; Koren, Stan; Whissell, Cynthia (Advances in Social Sciences Research Journal, 2018)
This research examines relationships between Google search behaviours (frequency of searches) and world geomagnetic and US market variables. Frequency of searches for the terms Anxiety, Depression, Peace, and Dow Jones were predicted with moderate success (p<.001, R values between .31 and .46) from the combination of variables. For example, more searches involving Anxiety were performed when geomagnetic activity along the East-West axis and trading volume were both high.